Thermoplasmonics with Gold Nanoparticles: A New Weapon in Modern Optics and Biomedicine - Guglielmelli, Alexa; Pierini, Filippo; Tabiryan, Nelson; Umeton, Cesare; Bunning, Timothy J.; De Sio, Luciano (Advanced photonics research, 2021)
Thermoplasmonics deals with the generation and manipulation of nanoscale heating associated with noble metallic nanoparticles. To this end, gold nanoparticles (AuNPs) are unique nanomaterials with the intrinsic capability to generate a nanoscale confined light‐triggered thermal effect. This phenomenon is produced under the excitation of a suitable light of a wavelength that matches the localized surface plasmonic resonance frequency of AuNPs. Liquid crystals (LCs) and hydrogels are temperature‐sensitive materials that can detect the host AuNPs and their photo‐induced temperature variations. In this perspective, new insight into thermoplasmonics, by describing a series of methodologies for monitoring, detecting, and exploiting the photothermal properties of AuNPs, is offered. From conventional infrared thermography to highly sophisticated temperature‐sensitive materials such as LCs and hydrogels, a new scenario in thermoplasmonic‐based, next generation, photonic components is presented and discussed. Moreover, a new road in thermoplasmonic‐driven biomedical applications, by describing compelling and innovative health technologies such as on‐demand drug‐release and smart face masks with smart nano‐assisted destruction of pathogens, is proposed. The latter represents a new weapon in the fight against COVID‐19. Gold nanoparticles are unique nanomaterials with the intrinsic capability to produce a considerable amount of heating upon illumination with a suitable resonant laser beam. The photo‐induced heat generated by gold nanoparticles—thermoplasmonic effect—offers several opportunities in different research fields ranging from advanced optical components to high‐precision medical applications. These cross‐disciplinary possibilities bring novel insight into light‐controlled applications.